What Is the de-qi-Related Pattern of BOLD Responses? A Review of Acupuncture Studies in fMRI - Sun, Jinbo (Hindawi Publishing Corporation, 2013)
de-qi, comprising mostly subjective sensations during acupuncture, is traditionally considered as a very important component for the possible therapeutic effects of acupuncture. However, the neural correlates of de-qi are still unclear. In this paper, we reviewed previous fMRI studies from the viewpoint of the neural responses of de-qi. We searched on Pubmed and identified 111 papers. Fourteen studies distinguishing de-qi and sharp pain and eight studies with the mixed sensations were included in further discussions. We found that the blood oxygenation level-dependent (BOLD) responses associated with de-qi were activation dominated, mainly around cortical areas relevant to the processing of somatosensory or pain signals. More intense and extensive activations were shown for the mixed sensations. Specific activations of sharp pain were also shown. Similar BOLD response patterns between de-qi evoked by acupuncture stimulation and de-qi-like sensations evoked by deep pain stimulation were shown. We reckon that a standardized method of qualification and quantification of de-qi, deeper understanding of grouping strategy of de-qi and sharp pain, and making deep pain stimulation as a control, as well as a series of improvements in the statistical method, are crucial factors for revealing the neural correlates of de-qi and neural mechanisms of acupuncture.